Ion-Molecule Collision Cross-Section Simulation using Linked-cell and Trajectory Parallelization - Cajahuaringa, Samuel; Zanotto, Leandro N.; Caetano, Daniel L. Z.; Rigo, Sandro; Yviquel, Hervé; Skaf, Munir S.; Araujo, Guido (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2022)
Ion Mobility coupled to Mass Spectrometry (IMMS) has become a highly valued tool for structural characterization of biological samples. In IM-MS the protein under investigation is ionized and accelerated by an electric field into a drift tube where it collides against a buffer gas. The separation of the gas-phase ions is then measured through the differences in their rotationally averaged Collision Cross-Section (CCS) values. The utility of the measured CCS for structural characterization critically depends on the validation against its theoretical calculation, which relies on intensive molecular mechanics simulation. Increasing the performance of CCS simulation is thus a relevant computational-chemistry research problem. This work shows that the combination of a linked-cell based algorithm with parallelization techniques can considerably increase the performance of CCS simulation. Experimental results reveal speedups from ~ 10× up to ~ 400× and parallelization efficiency greater than 0.98 when compared to High Performance Collision Cross Section (HPCCS), an optimized solution for CCS simulation. This reduces the CCS computation time from hours to minutes for a large range of proteins, making the proposed method the most performant approach to this problem nowadays, to the best of our knowledge.